Cell Biology of Plant Nematode Parasitism - Berg, R. Howard; Taylor, Chris (Plant Cell Monographs, 2009)
Plant-parasitic nematodes are among the most destructive plant pathogens, causing enormous losses to agronomic crops worldwide. This book provides an up-to-date review of research related to two of the most important nematode pests, root-knot and cyst nematodes. Chapters cover early plant-nematode interactions, identification of nematode proteins important in the establishment of nematode feeding sites, and classification of biochemical and signaling pathways significant in the development of specialized feeding sites in the host. The cellular and subcellular structures essential for parasitic interaction are examined using light and electron microscopy. Modern techniques of gene expression analysis and genomic sequencing promise to provide an even greater wealth of information to researchers, enabling them to develop and examine natural and manmade mechanisms of resistance to this important plant pest.